Rising incidence of unwed mothers in India; associated social parameters & institutional guidelines for managing them - Katke, Rajshree Dayanand; Saraogi, Mohit R.; Pagare, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Globally the incidence of unwed mothers is rising. While the incidence is higher in western countries, developing countries like India are soon catching up. Methods: Ours is a retrospective study from January 2009 to December 2013 analyzing 51 cases of unwed mothers for - changing incidence of unwed mothers in India, to look for predisposing social & family pressures which may have led to the pregnancy, to study neonatal outcomes in such mothers & to analyze the role of social worker intervention in the management of such pregnancies. Results: Our study showed a 50% rise in the incidence of unwed mothers in our institute over the years with a majority (49%) of them being teenaged girls. 68% unwed mothers were uneducated or had only primary education & 58.9% unwed mothers had some predisposing factor which might have contributed to the pregnancy. 52% unwed mothers (who delivered) opted for institutional admission till term and 35.4% of these underwent a caesarean section at term (higher than institute LSCS rates). 21.5% unwed mother united with father with social worker intervention. Conclusions: Social and demographic parameters play a significant role in the incidence of unwed mothers. Several of these parameters are subject to external regulation & can reduce incidence of unwed mothers. Also the role of a social worker is priceless in management of these patients.